In vitro Cell Migration and Invasion Assays - Justus, Calvin R.; Leffler, Nancy; Ruiz-Echevarria, Maria; Yang, Li V. (Journal of visualized experiments, 2014)
Migration is a key property of live cells and critical for normal development, immune response, and disease processes such as cancer metastasis and inflammation. Methods to examine cell migration are very useful and important for a wide range of biomedical research such as cancer biology, immunology, vascular biology, cell biology and developmental biology. Here we use tumor cell migration and invasion as an example and describe two related assays to illustrate the commonly used, easily accessible methods to measure these processes. The first method is the cell culture wound closure assay in which a scratch is generated on a confluent cell monolayer. The speed of wound closure and cell migration can be quantified by taking snapshot pictures with a regular inverted microscope at several time intervals. More detailed cell migratory behavior can be documented using the time-lapse microscopy system. The second method described in this paper is the transwell cell migration and invasion assay that measures the capacity of cell motility and invasiveness toward a chemo-attractant gradient. It is our goal to describe these methods in a highly accessible manner so that the procedures can be successfully performed in research laboratories even just with basic cell biology setup.